Using Linear Discriminant Analysis to Determine Ancestral Proportions of Admixed Individuals - Thill, Jordan; Kim, Ji Hyun (My University, 2015)
The purpose of this study was to create a model using linear liscriminant analysis to determine ethnic backgrounds based on chromosomal differences.
Color poster with text, images, charts, graphs, and tables.
Keywords: Hidden Markov Models; Ancestry; Genetic diseases; Linear discriminant analysis; Posters